The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/md19040185
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Phlorotannins and Gene Expression in the Brown Macroalga Fucus vesiculosus in Response to the Herbivore Littorina littorea

Abstract: Mechanisms related to the induction of phlorotannin biosynthesis in marine brown algae remain poorly known. Several studies undertaken on fucoid species have shown that phlorotannins accumulate in the algae for several days or weeks after being exposed to grazing, and this is measured by direct quantification of soluble phenolic compounds. In order to investigate earlier inducible responses involved in phlorotannin metabolism, Fucus vesiculosus was studied between 6 and 72 h of grazing by the sea snail Littori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Indeed, such compounds have been previously described in other species, such as Pleurophycus gardneri [ 66 ] and A. nodosum [ 65 ]. Moreover, according to Emeline et al [ 67 ], in Littorina littorea , upon the commencement of grazing activity, a significant increase in the gene expression of aryl sulfotransferase, an enzyme known to be involved in the sulfation of various compounds (including phenols), was observed in F. vesiculosus , which could be responsible for the sulfation of phlorotannins as part of its anti-grazing defense mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, such compounds have been previously described in other species, such as Pleurophycus gardneri [ 66 ] and A. nodosum [ 65 ]. Moreover, according to Emeline et al [ 67 ], in Littorina littorea , upon the commencement of grazing activity, a significant increase in the gene expression of aryl sulfotransferase, an enzyme known to be involved in the sulfation of various compounds (including phenols), was observed in F. vesiculosus , which could be responsible for the sulfation of phlorotannins as part of its anti-grazing defense mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the temporal effects of herbivore (sea snail Littorina littorea) predation upon Fucus vesiculosus has shown that tannins have a role as an inducible chemical defence upon grazing by the snails, and that grazing has differential temporal effects upon the stress response of the alga. 390 5 Red algae A Japanese Laurencia yielded two new C 15 acetogenins 936 and 937, 391 while a Soliera was the source of new aromatic polyketide 938. 392 An ethanolic extract of a Chinese L. tristicha was the source of 4-isopropylbenzaldehyde-containing products, presumably formed by condensation with acetophenone, as exemplied by 939.…”
Section: Reviewmentioning
confidence: 99%
“…Summarily, oxidative stress, herbivory activities, and UV-radiation are the central reported stimulants for phlorotannin secondary metabolite production. 57…”
Section: Phlorotannins As Potent Antioxidantsmentioning
confidence: 99%
“…Studies have implicated phlorotannins as an inducible metabolite, overproduced as an outcome of stress in several species of brown algae. 57,58 There is potential for some phlorotannins to act as insecticides based on their structural–function inference, although there are no studies at the time of this review to validate claims. Other bioactive roles from recent literature have shown phlorotannins to possess antioxidant, antimicrobial, anti-inflammatory, antiproliferative, antitumor, antidiabetic, radio-protective anti-adipogenic, and anti-allergic activities.…”
Section: Biological Roles Of Phlorotanninsmentioning
confidence: 99%
See 1 more Smart Citation